Toward Efficient and Sustainable River Basin Operational Services in Indonesia - World Bank Group (World Bank, Washington, DC, 2015)
Since the introduction of the Water Law in 2004, national river basin management in Indonesia has been carried out by 30 public river basin management organizations (RBOs), called either Balai Besar Wilayah Sungai(s) (BBWSs) or Balai Wilayah Sungai(s) (BWSs); the two are referenced together here as B(B)WSs. These national government agencies fill both regulatory and management functions, as well as undertaking construction, operation, and maintenance of river infrastructure and irrigation systems larger than 3,000 hectares. Provincial water agencies also provide water resource and river basin management in provincial basins and basins of national river territories, in coordination with the national river basin agencies.